Multidimensional perspective of social capital and quality of financial decision on corporate value: The case of Pakistan - Zhang, Jiewei; Ulllah, Hafeez; Diao, Xundi; Abbas, Hasnain (Frontiers in Environmental Science, 2022)
The study analyzes the impact of social and human capital on the corporate value of Pakistani enterprises listed on the stock exchange. The research specifically focused on Pakistan firms operating in the manufacturing sector. It assesses the moderating effect of QOFDP between social capital (SC) and human capital (HC) on corporate value. A quantitative analysis approach is applied to the primary data collected through a close-ended survey questionnaire from 600 supply chain employees of Pakistan manufacturing industry. Results were used to construct a quantitative inquiry approach for the primary data. The association and impact of social capital (SC) on the corporate value of manufacturing enterprises were found to be statistically significant, and it was also shown that Quality of financial decision and policy making (QOFDP) acted as a moderator between HC and corporate value. The moderating of QOFDP was exclusive to SC and HC, although all factors indicating SC (i.e., internal, and external network of social capital) and human capital (HC) affected company value positively and considerably. In light of the above findings, it has been advised that Pakistani manufacturing companies participate in rational financial decision-making to increase business sustainability and corporate value. However, this study is limited to the manufacturing industry in Pakistan and cannot be applied to other industries or nations.